A qualitative investigation of South African male child sex abuse victims' trauma narratives - Heylen, Chloé (My University, 2019)
Male Child Sex Abuse (MCSA) within South Africa is an underexplored area that warrants further investigation. Given the large amount of emphasis on female rather than male trauma narratives in sex abuse events, MCSA and its traumatic outcomes are often silenced in the public, psychological and academic domains. As a result of gendered constructions relating to sex abuse, the majority of MCSA victims fail to report their abuse and this results in low disclosure rates and consequently failure to seek treatment. This research analyses the discourse produced within trauma narratives of adult males who identify as Child Sex Abuse (CSA) victims. More particularly, this study aims to identify the influences of gender, trauma and sex abuse discourse on the construction of these narratives. This was achieved by drawing on semi-structured one-on-one interviews with seven participants, currently living in South Africa, who identified as adult male victims of CSA. Thereafter the transcripts were analysed using a Faircloughian (1989-1995) informed Critical Discourse Analysis (CDA) which allowed for the rigorous examination of how participants drew on childhood, gender and trauma discourses in order to validate their belonging to the category of male victimhood. Key findings revealed that trauma narratives are largely influenced by societal expectations of how trauma should manifest within victims of abuse. Further to this, participants revealed their own disbeliefs concerning the reality of male victimhood which is indicative of the influence of gendered constructions of masculinity within South Africa. By exploring the constructions of gender, trauma and sex abuse that emerge in narratives of childhood sex abuse and the ways that masculinity in South Africa influences this emergence, this study contributes to the growing literature in the CSA discipline and, in turn, to intervention possibilities for male victims of CSA.
This research report is submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the degree of Masters of Arts in Research Psychology, 2019
Keywords: Child abuse--South Africa; Male sexual abuse victims; Child sexual abuse